Combatting Substandard and Counterfeit Medicines in the Nigerian Drug Market: How Industrial Pharmacists Can Rise Up to the Challenge - Melody Okereke; Ignatius Anukwu; Sola Solarin; Mazi Sam Ohuabunwa (University of Minnesota Libraries Publishing, 2021)
Substandard and counterfeit medicines (SCMs) are a major public health threat in Africa. In Nigeria, the manufacture and distribution of substandard and counterfeit medicines in the drug market are booming, despite the efforts of law enforcement agencies to crack down on criminal syndicates over the years. The current situation has been exacerbated due to factors tied to unregulated open drug markets, lack of counterfeit detection technology, poor local pharmaceutical manufacturing capacity, and porous cross-border monitoring and surveillance systems. However, industrial pharmacists have a key role to play in combatting the production and circulation of SCMs in the Nigerian drug market. In this commentary, we examine the prevalence of SCMs in Nigeria and proffer feasible recommendations that industrial pharmacists can leverage to ensure its effective containment.